2015
DOI: 10.19104/jors.2015.102
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Treatment for Early Glottic Carcinoma

Abstract: The management of early glottic cancer has evolved significantly over the past two decades, with transoral laser microsurgery and radiotherapy emerging as the two favored modalities of treatment. Although the role of Open partial conservative surgery has reduced but there are still some specific indications. The preference of one modality over another has generated lot of debate and continues to be controversial. As the survival outcomes are similar in all the modalities, we need to consider factors like profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Due to the lack of prospective randomized controlled studies, there is no formal proof of the superiority of one treatment modality of early stage GSCC as regards the oncologic outcome or the functional outcome [11] [21]. Choice of treatment modality depends on three factors; local control, voice quality and cost [15] [22] in addition to treatment availability, expertise, and professional need for good voice quality [7]. Prior to 2013 treatment decisions at our institution were not based on the multidisciplinary approach, which explains why some of T1 glottic tumors in our study had surgery (minor surgery and even total laryngectomy in 2 patients) followed by radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the lack of prospective randomized controlled studies, there is no formal proof of the superiority of one treatment modality of early stage GSCC as regards the oncologic outcome or the functional outcome [11] [21]. Choice of treatment modality depends on three factors; local control, voice quality and cost [15] [22] in addition to treatment availability, expertise, and professional need for good voice quality [7]. Prior to 2013 treatment decisions at our institution were not based on the multidisciplinary approach, which explains why some of T1 glottic tumors in our study had surgery (minor surgery and even total laryngectomy in 2 patients) followed by radiation treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to RT, endolaryngeal surgery is voice-sparing, but can be easily repeated which makes it more available retreatment for local recurrence where it could be followed by RT [24]. There are limitations for TLM mainly the inadequate exposure on suspension microlayngoscopy, limited exposure of the glottis due to trismus, protruding teeth, anatomical variations of the upper and lower jaw, bulky tongue, cervical spondylosis, and previous surgery or radiotherapy to the neck [7]. The ENT-UK Head and Neck group reached a consensus that endoscopic excision is generally the preferred treatment for T1a GSCC, and suggested that it should be offered to GSCC tumors up to stage 2a [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation